2022
DOI: 10.34133/2022/9825237
|View full text |Cite
|
Sign up to set email alerts
|

The Regulatory Effect of Braided Silk Fiber Skeletons with Differential Porosities on In Vivo Vascular Tissue Regeneration and Long-Term Patency

Abstract: The development of small-diameter vascular grafts that can meet the long-term patency required for implementation in clinical practice presents a key challenge to the research field. Although techniques such as the braiding of scaffolds can offer a tunable platform for fabricating vascular grafts, the effects of braided silk fiber skeletons on the porosity, remodeling, and patency in vivo have not been thoroughly investigated. Here, we used finite element analysis of simulated deformation and compliance to des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 77 publications
(98 reference statements)
0
15
0
Order By: Relevance
“…Previous studies on artificial blood vessels have focused more on the cellularization within the grafts [ 32 , 33 ], or the endothelialization and intimal hyperplasia on the luminal surface [ 34 , 35 ], paying less attention to neovascularization surrounding the grafts. Vascular networks play a crucial role in transporting blood, delivering oxygen and providing nutrients to tissues at the microvasculature interface.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on artificial blood vessels have focused more on the cellularization within the grafts [ 32 , 33 ], or the endothelialization and intimal hyperplasia on the luminal surface [ 34 , 35 ], paying less attention to neovascularization surrounding the grafts. Vascular networks play a crucial role in transporting blood, delivering oxygen and providing nutrients to tissues at the microvasculature interface.…”
Section: Discussionmentioning
confidence: 99%
“…172 Experimental evidence has shown that maintaining compliance and nonlinearity contributes to improved graft performance during in vivo implantation. 54,101,112,117,162 3.2.3. Long-Term Performance.…”
Section: Fibrous Tissue Engineering Vascular Graftmentioning
confidence: 99%
“…Szczesny et al explored the influence of bending fibers on graft mechanical properties using the neo-Hookean matrix model. , Bas et al conducted simulations on soft network composite materials, demonstrating the resilience of curving fibers . Ding et al employed finite element analysis to establish a model investigating the relationship between graft compliance and braided tube porosity, providing guidance for braided tube preparation . Xu et al.…”
Section: Nonlinear Elasticity Of Vascular Graftsmentioning
confidence: 99%
See 1 more Smart Citation
“…Silk fibroin (SF) is widely used in medical fields such as vascular stents, medical cosmetology, and wound dressing, and so on and has good biocompatibility [ [11] , [12] , [13] , [14] , [15] ]. SF is slightly soluble in water due to its high degree of crystallization [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%